Cloud Data Security by Hybrid Machine Learning and Cryptosystem Approach - Shukla, Aditya Kumar; Sharma, Ashish (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Cloud computing is a key platform for achieving secure data exchange and offering increased data storage with no additional burden. Cloud environments provide these benefits. In order to achieve greater levels of security inside a cloud environment, one of the most important aspects of cloud service provisioning is the prevention of data breaches caused by unauthorized access to personal information. There are still many security measures that have not been refined to an acceptable level. To address this issue, we provide an unique machine learning programme that use cryptographic techniques to protect data both while it is being stored in the cloud and while it is being accessed. According to the results of the study, the suggested approach has attained a sensitivity of 87.5%, an F1-score of 93.5%, and a specificity of 97.5%.